2015
DOI: 10.1016/j.jaut.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

B cell expression of the SH2-containing inositol 5-phosphatase (SHIP-1) is required to establish anergy to high affinity, proteinacious autoantigens

Abstract: Many self-reactive B cells exist in the periphery in a rapidly reversible state of unresponsiveness referred to as anergy. Reversibility of anergy indicates that chronically occupied BCR must transduce non-durable regulatory signals that maintain unresponsiveness. Consistent with such a mechanism, studies of immunoglobulin transgenic, as well as naturally occurring polyclonal autoreactive B cells demonstrate activation of the inositol 5-phosphatase SHIP-1 in anergic cells, and low affinity chromatin autoantige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
34
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 33 publications
6
34
3
Order By: Relevance
“…Indeed, expression and/or function of PTEN or SHIP1, phosphatases that antagonize the PI3K pathway, are increased in anergic B cells (Browne et al, 2009;O'Neill et al, 2011;Smith et al, 2019). Similarly, expression of constitutively active p110α, deletion of PTEN or SHIP1, or overexpression of CD19, one of the B cell coreceptors that recruits and activates PI3K, all disrupt B cell tolerance (Akerlund et al, 2015;Browne et al, 2009;Greaves et al, 2019;Inaoki et al, 1997;Leung et al, 2013). However, the break in tolerance we observed here differs in multiple ways from these previous findings.…”
Section: Discussionsupporting
confidence: 44%
“…Indeed, expression and/or function of PTEN or SHIP1, phosphatases that antagonize the PI3K pathway, are increased in anergic B cells (Browne et al, 2009;O'Neill et al, 2011;Smith et al, 2019). Similarly, expression of constitutively active p110α, deletion of PTEN or SHIP1, or overexpression of CD19, one of the B cell coreceptors that recruits and activates PI3K, all disrupt B cell tolerance (Akerlund et al, 2015;Browne et al, 2009;Greaves et al, 2019;Inaoki et al, 1997;Leung et al, 2013). However, the break in tolerance we observed here differs in multiple ways from these previous findings.…”
Section: Discussionsupporting
confidence: 44%
“…Besides allowing more definitive analysis of the requirements for maintaining anergy, use of anergic B cells that were allowed to develop normally before acute induction of alterations in inhibitory signaling eliminated influences of confounding developmental effects. Although our findings regarding the role of SHIP-1 in anergy are consistent with previously published work using mb-1cre-driven deletion of SHIP-1 (O'Neill et al, 2011;Akerlund et al, 2015), they pinpoint the function of SHIP-1 to maintenance of anergy. Although SHP-1 was shown previously to be essential for maintenance of tolerance (Pao et al, 2007), its role in B cell anergy was unclear (Cyster and Goodnow, 1995).…”
Section: Discussionsupporting
confidence: 92%
“…6). This is consistent with a reported disability of anergic B cells to accumulate PI(3,4,5) P3 in their membrane upon BCR stimulation (Browne et al, 2009), the observed increase in SHIP-1 activity (O'Neill et al, 2011;Akerlund et al, 2015), and increased PTEN expression (Browne et al, 2009) in anergic B cells. The fact that the PI3K pathway promotes plasma cell differentiation (Omori et al, 2006) fits with the observed autoantibody response seen when inhibition of the PI3K pathway is relieved.…”
Section: Discussionsupporting
confidence: 91%
“…While deletion of SHIP in B cells does not lead to lung and gut inflammation, it does lead to the development of a chronic autoantibody-mediated disease similar to Systemic Lupus Erythematosus (SLE) [89]. Deletion of SHIP in BCR-transgenic B cells specific for Ars or HEL antigens was found to reverse their anergic phenotype in two models of self-tolerance [89,90]. We found that B cells bearing mutations uncoupling the TAPP adaptors from PI(3,4)P 2 were hyper-active and drive an SLE-like phenotype [51], suggesting that proteins binding this SHIP enzymatic product may contribute important regulatory functions.…”
Section: Role Of Ship In Autoimmune and Inflammatory Diseasementioning
confidence: 99%